Enhancing device efficiencies of solid-state white light-emitting electrochemical cells by employing waveguide coupling. Issue 22 (14th June 2015) - Cheng, Chia-Yu; Wang, Chi-Wei; Cheng, Jing-Rong; Chen, Hsiao-Fan; Yeh, Yun-Shiuan; Su, Hai-Ching; Chang, Chih-Hao; Wong, Ken-Tsung
<x xml:space="preserve">Abstract</x> Device efficiency of white LECs can be enhanced by recycling the trapped EL in the ITO layer to the forward direction.